RFID-WSN Integrated Architecture for Energy and Delay- Aware Routing A Simulation Approach - Ahmed, Jameel; Siyal, Mohammed Yakoob; Tayyab, Muhammad; Nawaz, Menaa; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2015)
The book identifies the performance challenges concerning Wireless Sensor Networks (WSN) and Radio Frequency Identification (RFID) and analyzes their impact on the performance of routing protocols. It presents a thorough literature survey to identify the issues affecting routing protocol performance, as well as a mathematical model for calculating the end-to-end delays of the routing protocol ACQUIRE; a comparison of two routing protocols (ACQUIRE and DIRECTED DIFFUSION) is also provided for evaluation purposes. On the basis of the results and literature review, recommendations are made for better selection of protocols regarding the nature of the respective application and related challenges. In addition, this book covers a proposed simulator that integrates both RFID and WSN technologies. Therefore, the manuscript is divided in two major parts: an integrated architecture of smart nodes, and a power-optimized protocol for query and information interchange.
Introduction -- RFIDs and WSNs -- Challenges and Issues in the WSN and RFID -- The Delay Model for Acquire -- Simulator for Smart Node -- Simulation Based Case Study and Analysis.
Keywords: Engineering; Computer organization; Electrical engineering; Power electronics; Engineering; Communications Engineering, Networks; Computer Systems Organization and Communication Networks; Power Electronics, Electrical Machines and Networks; Electronic books